Community-Oriented Policing and Technological Innovations - Leventakis, Georgios; Haberfeld, M. R. (SpringerBriefs in Policing, 2018)
Community-Oriented Policing; Police Studies; Policing and Technology; Predictive Policing; Policing Innovations; Crime Prevention and Intervention; Crime Detection; Fear of Crime; Urban Security